2013
DOI: 10.1128/mmbr.00054-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of Antibiotic Biosynthesis in Streptomyces

Abstract: SUMMARY Streptomycetes are the most abundant source of antibiotics. Typically, each species produces several antibiotics, with the profile being species specific. Streptomyces coelicolor , the model species, produces at least five different antibiotics. We review the regulation of antibiotic biosynthesis in S. coelicolor and other, nonmodel streptomycetes in the light of recent studies. The biosynthesis of each antibiotic is specified by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
560
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 609 publications
(573 citation statements)
references
References 300 publications
(412 reference statements)
6
560
2
5
Order By: Relevance
“…The initiation of antibiotic biosynthesis is controlled at several levels genetically (Liu et al, 2013). The most basic and specific control involves genes encoding regulators that work only on one biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of antibiotic biosynthesis is controlled at several levels genetically (Liu et al, 2013). The most basic and specific control involves genes encoding regulators that work only on one biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 15 N-JadX bound Cm at both pH values, with minimal loss in signal intensities ( Figure S19). With Water-LOGSY results comparable at pH 6.6 and 7.6, a series of 1 curve ( Figure 6D) that was fit using nonlinear regression (Equation S2). 48 The measured K d value of 232 ÎŒM was lower than that observed with the WaterLOGSY methodology and significantly tighter than the nonspecific binding 48 we have recently observed for JdDS interactions with a series of unrelated enzymes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast to the moe genes, the tchm genes do not contain TTA codons, which are known to limit moenomycin production at the translational level, in their coding sequences (Makitrynskyy et al, 2013). In general, tRNA Leu UAA (encoded by bldA gene) is an important and widespread regulatory switch in Streptomycetes Chandra and Chater 2008;Liu et al 2013). It is likely that the tchm cluster is not subject to direct bldA control.…”
Section: Annotation and Analysis Of The Teichomycin Gene Clustermentioning
confidence: 99%